2005
DOI: 10.1107/s0021889804032662
|View full text |Cite
|
Sign up to set email alerts
|

Solving molecular crystal structures from laboratory X-ray powder diffraction data withDASH: the state of the art and challenges

Abstract: The crystal structures of 35 molecular compounds have been redetermined from laboratory monochromatic capillary transmission X-ray powder diffraction data using the simulated-annealing approach embodied within the DASH structure solution package. The compounds represent industrially relevant areas (pharmaceuticals; metal coordination compounds; nonlinear optical materials; dyes) in which the research groups in this multi-centre study are active. The molecules were specifically selected to form a series within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 36 publications
(33 reference statements)
3
79
0
3
Order By: Relevance
“…33 One may go so far as to say that SDPD has lived up to its ''routine'' designation, 12,25 but the technique does have limitations and determinations may fail, typically when the data cannot be indexed or when the starting molecular model is deficient in some respect. It is also significant that the upper limit of effectiveness of the SA algorithm has yet to be established, although a previous investigation 33 demonstrated that, given XRPD data collected to 2 Å resolution or better: (a) structures with <15 DOF present little challenge, yielding accurate structure solutions reproducibly; (b) for structures with greater complexity (DOF ¼ 15-20), where the preponderance of local minima in the agreement hypersurface reduces the frequency of success, the SA algorithm is still able to locate the global minimum with a reasonable frequency. Higher levels of complexity (DOF > 20) remain to be explored systematically; hence g-CBZ and CT-DMF2 represent significant contributions to this wider effort (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…33 One may go so far as to say that SDPD has lived up to its ''routine'' designation, 12,25 but the technique does have limitations and determinations may fail, typically when the data cannot be indexed or when the starting molecular model is deficient in some respect. It is also significant that the upper limit of effectiveness of the SA algorithm has yet to be established, although a previous investigation 33 demonstrated that, given XRPD data collected to 2 Å resolution or better: (a) structures with <15 DOF present little challenge, yielding accurate structure solutions reproducibly; (b) for structures with greater complexity (DOF ¼ 15-20), where the preponderance of local minima in the agreement hypersurface reduces the frequency of success, the SA algorithm is still able to locate the global minimum with a reasonable frequency. Higher levels of complexity (DOF > 20) remain to be explored systematically; hence g-CBZ and CT-DMF2 represent significant contributions to this wider effort (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…[24] CCDC 790342 contains the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/ data_request/cif.…”
Section: Methodsmentioning
confidence: 99%
“…The example concerns the phenylacetic acid (pharmaceutical compound) C 8 H 8 O 2 structure [50]: monoclinic, P 2 1 /a , 2 experimental range (5-65) • , 258 reflections, RES = 1.43 Å; medium quality laboratory data; two O and eight C atoms in the asymmetric unit. The first phasing set (ranked according to CFOM), automatically selected by the program for the Fourier map calculation, does not supply the correct solution which is instead provided by the fifth one (as obtained by the automatic procedure exploring all the phasing trials).…”
Section: Examplementioning
confidence: 99%